Decoupling Economic Growth from Ecological Impact: A Socio-Ecological Modeling of Small-Scale Fisheries in the Post-Pandemic Era - Anna Dara; Lucas Wong; Ava Lee; Ziad Khalil (Journal of Multidisciplinary Sustainability Asean, 2026)
Background Small-scale fisheries are vital for coastal communities but face increasing challenges from overfishing, degradation, and economic instability, all of which were exacerbated by the COVID-19 pandemic. Purpose This research aims to decouple economic growth from ecological impact in small-scale fisheries by creating a socio-ecological model that integrates both economic and ecological variables for sustainable management. Method The study employs a mixed-methods approach, combining socio-economic surveys, interviews with key stakeholders, and ecological data collection to build the integrated framework. Results Regions adopting sustainable practices demonstrated resilience in both ecological and economic recovery post-pandemic, while regions relying on unsustainable practices continued to face decline. Conclusion Long-term sustainability requires a balanced approach that combines financial incentives, sustainable practices, community engagement, and integrated policies supporting both economic recovery and environmental conservation.